INVESTING IN PRECIOUS STONES: RISKS AND PROSPECTS (American Journal of Technology and Applied Sciences, 2025)
This article examines the key characteristics of the precious stone market (diamonds, rubies, sapphires, emeralds, etc.) as an asset class: liquidity, profitability, pricing factors, risks (price volatility, counterfeiting, regulatory and reputational risks), and prospects (growing demand for colored stones, the impact of lab- grown diamonds, sustainable development, and supply chain transparency). A review of empirical studies on profitability and volatility is provided, along with a discussion of practical recommendations for investors.